Ceftobiprole for the treatment of infective endocarditis: A case series. (March 2020) - Tascini, Carlo; Attanasio, Vittorio; Ripa, Marco; Carozza, Antonio; Pallotto, Carlo; Bernardo, Mariano; Francisci, Daniela; Oltolini, Chiara; Palmiero, Giulia; Scarpellini, Paolo
Highlights: Staphylococcal endocarditis has still elevated morbidity and mortality. Ceftobiprole and daptomycin have a synergistic activity against S. aureus . Ceftobiprole is a promising alternative treatment for infective endocarditis. Ceftobiprole–daptomycin combination is a promising alternative treatment for IE. Abstract: Objectives: Ceftobiprole is a relatively new cephalosporin with broad-spectrum activity and good tolerability. Despite its promising characteristics, to our knowledge, only two case reports, previously published also by some of us, is available concerning its administration for the treatment of infective endocarditis. Hereby we report our experience in this field. Methods: All the patients with infective endocarditis treated with ceftobiprole were enrolled. Results: 12 cases of endocarditis were treated with ceftobiprole, 11/12 in combination with daptomycin and 1/12 as monotherapy. Gram-positive bacteria were isolated in 12/12 patients; 3 cases were polymicrobial. Cure rate was 83% (10/12 patients). In 9/12 (75%) cases, patients were switched to ceftobiprole following failure of previous antimicrobial regimen. In 3/3 patients in which ceftobiprole was administered because of persistently positive blood culture, bacteraemia clearance was rapidly achieved. Conclusions: Ceftobiprole, especially in combination, could be a promising alternative treatment for infective endocarditis.